Níquel em solo e plantas de milho cultivadas em área tratada com lodo de esgoto durante 15 anos consecutivos - Alves, Suelen Cristina Nunes [UNESP] (2014)
The waste solid urban production waste is growing because the steady population has increase. One of these residues is the sewage sludge (SS). This residue has been shown to be a good alternative for fertilization of agricultural soils, because it is a material rich in nutrients for plants and potential source of organic matter. Sewage sludge must be managed with caution because it contains metals, pathogens and toxic organic compounds in their constitution, to aim the environmentally sustainable use. The objective of this study was to quantify the Ni element and the pseudo-total content available in organic matter fractions (humic acid, fulvic acid). In addition, we evaluated the soil Ni adsorption and evaluated the absorbed by corn plants. The experiment was conducted in field conditions at UNESP - Jaboticabal experimental area. The design was a complete randomized block with four treatments and five replications. The treatments were, T0 - no sludge, T5 - 5 t.ha-1 of SS, T10 - 10 t.ha-1 of SS and T20 - 20 t.ha-1 of SS. The used sludge had its origin from the sewage treatment station, ETE-SABESP located in Monte Alto, SP. In the depth from 0.05 to 0.10 m, the pseudo-total content of Ni was increased from 75.9 to 107.3 mg.kg-1 depending of sludge doses, while the available Ni content has not been changed. In organic matter fractions, the surface layer was the one that showed the highest levels of Ni, for both humic acid and fulvic acid, with significant at 0.05 - 0.10 m. The results of adsorption performed was adjusted to Freundlich’s isotherm with coefficients of determination greater than 0.90. The Ni at the diagnosis leaf ranged between 0.093 (T10) - 0.611 mg.kg-1 (T5). No amounts of Ni were detected on whole plant and grain. The maize grain yield on the area that received sewage sludge for 15 years, ranged around 14.86 to 19.26 t.ha-1, corrected to 13% of moisture and did not differ ...